Pengaruh Penambahan Serat Ampas Tebu Sebagai Tulangan Micro pada Beton - Itteridi, Vike; Edowinsyah, Edowinsyah; Andreson, Ganda (Universitas Batanghari Jambi, 2024)
Based on this research, concrete has high compressive strength but low flexural strength. There-fore, the addition of sugarcane bagasse fibers is carried out as an additive to overcome the low flexural strength issue in concrete. This study aims to determine the effect of adding sugarcane bagasse fibers on the characteristics of concrete, including compressive and flexural strength. Fiber-reinforced concrete is a composite material consisting of regular concrete and other mate-rials, such as natural or artificial fibers. The method used in this research is an experimental method, adding 1% of sugarcane bagasse fibers by weight of cement to the normal concrete with a target strength of F'c 19.3 MPa and fiber length of 5 cm. The samples used in this research are concrete cylinders and beams tested using a Universal Testing Machine. The research results show that the optimum compressive strength of normal concrete is 20.36 MPa at 28 days of age. Meanwhile, for fiber-reinforced concrete BSTC and BSTH, the compressive strengths are 17.83 MPa and 16.49 MPa, respectively, indicating a decrease compared to the normal concrete. This decrease is attributed to the addition of sugarcane bagasse fibers, which are lightweight addi-tives and not solid aggregates, resulting in some voids in the sugarcane bagasse fibers. The re-sults of the flexural strength testing show that the optimum flexural strength of BSTC is 4.44 MPa, and for BSTH, it is 4.09 MPa, while the normal concrete (BN) only achieves 3.61 MPa. This is due to the increased bonding effect in concrete caused by the addition of fibers, which helps to resist the occurrence of cracks during flexural testing